Advances in RSV vaccine research and development – A global agenda. Issue 26 (3rd June 2016) - Higgins, Deborah; Trujillo, Carrie; Keech, Cheryl
Highlights: RSV is a significant annual cause of lower respiratory tract illness globally. Pediatric and elderly populations are most vulnerable, but no vaccine exists. The current state of RSV vaccine research and development is summarized. 60 RSV vaccine candidates in development, of which 16 are in Phase 1–3 trials. Abstract: Respiratory syncytial virus (RSV) is an important cause of viral lower respiratory tract illness in infants and children globally, but no vaccine is currently available to protect these vulnerable populations. Live-attenuated vaccine approaches have been in development for decades, but achieving the appropriate balance between immunogenicity and safety has proven difficult. Immunoprophylaxis with the neutralizing monoclonal antibody palivizumab is limited to high-risk infants, but cost requirements for multiple dosing make its use impractical in low- and middle-income countries. A growing number of RSV vaccine candidates using a variety of technologies and targeting diverse populations has emerged in recent years. There are now 60 RSV vaccine candidates in development that target pediatric and elderly populations. While most are at a preclinical stage, 16 candidates are in clinical development. This review summarizes current RSV vaccine research and development, including an overview of the vaccine platforms being used, the development stage of individual vaccine candidates, and gaps to be addressed to facilitate use of these vaccines to meet global health needs.